Capturing the design space of meaningful human control in military systems using repertory grids - van Diggelen, Jurriaan; Burken, Christine Boshuijzen-van; Vince, Julian (Frontiers in Psychology, 2025)
This study explores the design space of meaningful human control (MHC) for military AI systems using the repertory grid technique (RGT) to capture expert perspectives across disciplines. By interviewing twelve experts from fields such as military, engineering, philosophy, and human factors, we identified key constructs related to autonomy, moral sensitivity, destructiveness, and human-machine interaction. The findings reveal both consensus and variation in experts’ understanding of MHC, highlighting challenges in interdisciplinary alignment. The study identifies key variables for MHC and uses them to create a design map that guides system designers in integrating MHC concepts into AI applications. By establishing a shared vocabulary and improved elicitation methods, we aim at facilitating future discussions and research aimed at establishing and maintaining MHC.